The Effect of Consumer Satisfaction and Trust on Purchasing Behavior at Shopee E-Commerce - Sukma aminati septia -; Tabita Kamilia; Tessalonika Vanera Rajagukguk; Jihan Hasanah Nasution Nasution; Santa Maria br Tarigan (PT. Altaf Publishing Corp, 2025)
This study examines the impact of online shopping satisfaction and customer trust on purchasing behavior in the Shopee e-commerce platform. The research employs descriptive and associative methods with a quantitative approach. The population comprises Business Management students from Politeknik Negeri Medan, with 40 respondents selected based on specific criteria. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that online shopping satisfaction (X1) and customer trust (X2) have a positive and significant effect on purchasing behavior (Y), contributing 76.2%. The coefficient of determination (R2) of 58.1% suggests that these independent variables explain most of the variation in purchasing behavior. The findings highlight the crucial role of shopping experience satisfaction and trust in influencing consumer purchasing decisions. Therefore, Shopee should continuously enhance service quality and transaction security to maintain customer loyalty. Future research with a broader scope and qualitative or mixed-method approaches may provide deeper insights into other factors affecting consumer purchasing behavior.